Studi Perbandingan selenoid kapiler dan selenoid ekspansi pada Mesin Es serta di kontrol Aplikasi Blynk - Mustofa, Adi; ujang wiharja (Universitas PGRI Palembang, 2023)
Currently, the use of this ice machine still uses a solenoid connected to a capillary and the results cannotbe targeted. The use of an ice machine with the ESP8266 module is combined with the blynk applicationwhich is a combination with the Internet of Thinks (IoT) system which makes the performance of using theice machine can be run remotely or with a smartphone. Reduced costs and less operator effort to expendfor ice making. The ice machine was finally integrated with the ESP8266 Module, the blynk applicationand added with one solenoid connected to an expansion which functions as a substitute for the capillaryselenoid if the need for ice is needed quickly in the process and will return to the capillary selenoid duringnormal production. The results showed that the ice machine with capillary selenoid was slower in the iceproduction process with 1 hour of production time of 5 kg of ice and required electricity consumptionduring production of 0.814 KWH, while the ice machine after using selenoid expansion the machineproduction process was faster than the capillary selenoid system by producing ice production for 1 hourwith a yield of 8 kg of ice and requires electricity consumption during production of 0.855 KWH, withpressure for expansion of 18 bar.